INVESTIGATING KURDISH EFL STUDENT TEACHERS’ CLASSROOM TEACHING EXPERIENCES AND PROBLEMS DURING TEACHING PRACTICE - MOHAMMAD, ZAKI H.; AL-AZZAWI, MOHAMED BASIL. (Journal of Duhok University, 2023)
Teaching practice (TP), also known as teaching practicum, is a compulsory component of every teacher education program. In recent years, multiple studies have attempted to understand student teachers’ school-based teaching practice challenges. However, there has been insufficient investigation into the classroom experiences and challenges of the student teachers. This study aims to investigate the English language student teachers’ classroom teaching experiences and problems they face during teaching practice at four public colleges of education and basic education in Duhok, Kurdistan region of Iraq (KRI). A 31-item questionnaire (paper and online) categorized into four domains - problems related to: student teachers (STs), classroom students, textbooks, and classroom environment-was administered to 132 participants at the end of their TP. The study revealed that student teachers encountered a wide range of challenges most of which were caused by the classroom students and classroom environment while less frequently by textbooks and STs themselves. These results allow us to understand the nature of the problems that handicap a productive and impactful TP course that aims to develop the skills of student teachers. These findings should provide a promising data framework for future plans of teaching practice